KEMAMPUAN MAHASISWA BUDIDAYA PERAIRAN MENGGUNAKAN APLIKASI SPSS (STATISTICAL PRODUCT AND SERVICE SOLUTIONS) DALAM PEMBELAJARAN STATISTIKA : The Ability Of Aquatic Cultivation Students To Use SPSS (Statistical Product and Service Solutions) Applications In Learning Statistics - Aminullah Aminullah (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Statistics is a subject related to data collection, processing, analysis, and interpretation. Data processing, which requires specific formulas, is prone to errors when done manually and is time-consuming. Therefore, supporting applications such as SPSS are essential. The purpose of this study was to determine the ability of aquaculture students to use SPSS in statistics learning. This research was a survey with a quantitative descriptive approach. This study was conducted at Universitas 45 Mataram, involving 12 students in the Aquaculture class. Data collection used in this study was student observation sheets for SPSS practice, and descriptive statistics were used as data analysis techniques. The results showed that the highest percentage of students using SPSS (41.67%) was considered moderate. One student, or 8.33%, still had low ability. This low ability was due to low attendance, lack of laptops for practice, and limited awareness of asking questions or discussing, as well as limited independent learning. Lecturers provide remedial or special treatment in the form of additional meetings to address low ability. There are also 16.67%, or two, students with very high ability.